Antara Damiens dan Pieter Erberveld: Sebuah Perbandingan “Teater” Kekejaman - Suyono, Seno Joko (Sekolah Pascasarjana Institut Kesenian Jakarta, 2018)
The story teller’s point of view in a literary piece can demonstrate a poet’s alignment. Through the point of view, it is quite often literary piece is turned to a propaganda tool for a poet to convey his/her mission and thought to influence people, especially the readers. This article discusses the character Damiens and Pieter Erberveld with two different author’s point of views using comparative method in the form of text analysis. Through the analysis of point of view and characterization, there are two different perspectives toward the character of Pieter Erberveld. The result of the analysis is that the character of Pieter Erberveld is described as treason in Malay literature, but it is the opposite when it is seen from the perspective of Japanese literary world, this character is a hero.Sudut pandang pencerita dalam sebuah karya sastra dapat menunjukkan keberpihakan seorang penyair. Lewat sudut pandang itu, tidak jarang pula karya sastra dijadikan alat propaganda bagi seorang penyair untuk menyampaikan misi dan pemikirannya untuk memengaruhi masyarakat, khususnya penikmat karya itu. Tulisan ini membahas tentang tokoh Damiens dan Pieter Erberveld lewat dua sudut pandang kepengarangan yang berbeda dengan menggunakan metode komparasi melalui analisis teks. Lewat analisis sudut padang dan penokohan, didapatkan dua pespektif yang berbeda terhadap tokoh Pieter Erberveld. Dari hasil analisis, tokoh Pieter Erberveld digambarkan sebagai sosok makar dalam kesusastraan Melayu. Sementara itu, dalam kesusastraan Jepang, tokoh tersebut dipandang sebagai seorang hero.